PERCEIVED ORGANIZATIONAL SUPPORT EFFECT, REWARDS ANDRECOGNITION, AND SPIRITUALITY ON EMPLOYEE ENGAGEMENT - Frinlicia Frinlicia; B Medina Nilasari (Universitas Trisakti, 2016)
The problems of this research were to examine the influence of perceived organizational support, rewards and recognition and spirituality on employee engagement.. The objectives of this research were to examine whether: (1) perceived organizational support affect employee engagement; (2) rewards and recognition affect employee engagement; (3) spirituality affect employee engagement and (4) perceived organizational support, rewards and recognition and spirituality affect employee engagement. The methodology of this research was a statistical descriptive and hypotheses testing to study the relationship. A survey questionnaire was developed and validated. Purposive sampling was used to select the sample. A total 167 questionnaire were distributed and 167 valid responses collected. Regression analysis was used to predict and estimate the relationship. The result from this study indicate that perceived organizational support, rewards and recognition and spirituality has a positive and significant effect on employee engagement. Research limitation in this research was that this study was used self-report data so the responses provided may be less objective and this study was weak generalization because the data collected limited on the sample of millennials generation of PT Bank Central Asia, Tbk